Remarks on Dadanitic MḤR. With an Addendum on the Word H' in AH 288 - Hidalgo-Chacón Díez, María del Carmen (Journal of Semitic studies, 2017)
In the Dadanitic inscriptions from the oasis of al-‘Ulā, in the northwest part of Saudi Arabia, the word mḤr occurs three times (AH 209, AH 288 and JSLih 37). Previous editors have proposed various interpretations, none of which is very satisfactory. The grammatical function of this word and, to some extent, the contexts in which it appears, show that it needs to be considered in another way. The aim of this article is to clarify its meaning in the light of a new analysis of the inscriptions in which it appears.